Emerging facets of prokaryotic glycosylation - Schäffer, Christina (FEMS Microbiol Rev, 2016)
Glycosylation of proteins is one of the most prevalent post-translational modifications occurring in nature, with a wide repertoire of biological implications. Pathways for the main types of this modification, the N- and O-glycosylation, can be found in all three domains of life—the Eukarya, Bacteria and Archaea—thereby following common principles, which are valid also for lipopolysaccharides, lipooligosaccharides and glycopolymers. Thus, studies on any glycoconjugate can unravel novel facets of the still incompletely understood fundamentals of protein N- and O-glycosylation. While it is estimated that more than two-thirds of all eukaryotic proteins would be glycosylated, no such estimate is available for prokaryotic glycoproteins, whose understanding is lagging behind, mainly due to the enormous variability of their glycan structures and variations in the underlying glycosylation processes. Combining glycan structural information with bioinformatic, genetic, biochemical and enzymatic data has opened up an avenue for in-depth analyses of glycosylation processes as a basis for glycoengineering endeavours. Here, the common themes of glycosylation are conceptualised for the major classes of prokaryotic (i.e. bacterial and archaeal) glycoconjugates, with a special focus on glycosylated cell-surface proteins. We describe the current knowledge of biosynthesis and importance of these glycoconjugates in selected pathogenic and beneficial microbes.